2020
DOI: 10.3390/ijerph17103645
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Usefulness of the Inhibitory Control Test (ICT) in the Diagnosis of Minimal Hepatic Encephalopathy

Abstract: Background: Minimal hepatic encephalopathy (MHE) refers to a number of neuropsychiatric and neurophysiological disorders in patients with cirrhosis who do not show abnormalities on physical examination or in clinical tests. The aim of this study was to determine the prevalence, risk factors, and predictive value of minimal hepatic encephalopathy and the usefulness of the inhibitory control test (ICT) in the diagnosis. Methods: Seventy patients (mean age 53 years, range 24−77) with liver cirrhosis were enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…After duplicates were removed, a total of 48 studies were identified in the present study, of which 36 were excluded from the analysis according to the inclusion and exclusion criteria; the remaining 12 studies 6,9–19 were included in the systematic review (Figure 2). The characteristics of these 12 studies are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After duplicates were removed, a total of 48 studies were identified in the present study, of which 36 were excluded from the analysis according to the inclusion and exclusion criteria; the remaining 12 studies 6,9–19 were included in the systematic review (Figure 2). The characteristics of these 12 studies are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of these 12 studies are presented in Table 1. Three 6,10,19 of 12 studies were published before 2010, and nine studies 9,11–18 were published after 2010. All 12 studies 6,9–19 enrolled patients with different etiologies of liver cirrhosis, including viral hepatitis, alcohol hepatitis, autoimmune hepatitis, nonalcoholic steatohepatitis, primary biliary cirrhosis, primary sclerosing cholangitis, and cryptogenic cirrhosis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations